2010
DOI: 10.1371/journal.pone.0012914
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Lifestyle and Behaviour: A Survey from a Developing Country

Abstract: IntroductionAdolescents form two-thirds of our population. This is a unique group of people with special needs. Our survey aims to identify the lifestyle and behavioral patterns in this group of people and subsequently come up with issues that warrant special attention.MethodsA survey was performed in various schools of Karachi. Data collection was done via a face-to-face interview based on a structured, pre-tested questionnaire. Participants included all willing persons between 12–19 years of age.ResultsMost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 33 publications
1
44
0
5
Order By: Relevance
“…Back pain arising from improper use of the body in activities of daily life develops over several years, starting in the school phase and extending throughout life, and the pain deteriorates to the extent that inactivity has become prevalent in current society [28]. Behaviors during developmental years can influence future health risk in later life; therefore young people are considered an important target group for early detection of health problems [29]. Effect on Back Pain Occurrence Among School Children…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Back pain arising from improper use of the body in activities of daily life develops over several years, starting in the school phase and extending throughout life, and the pain deteriorates to the extent that inactivity has become prevalent in current society [28]. Behaviors during developmental years can influence future health risk in later life; therefore young people are considered an important target group for early detection of health problems [29]. Effect on Back Pain Occurrence Among School Children…”
Section: Significance Of the Studymentioning
confidence: 99%
“…However, these rates are not representative of the population as they were based on the very small subset of people who have access to mental health services. Another cross-sectional study on 12-19 years old school going adolescents found 17% prevalence of depression as assessed by DSM based unstandardized interview (Qidwai et al, 2010). Other developing countries in the region exploring rates of mental health problems report varying results.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Failure to consume a nutritionally balanced diet at this decisive point in life not only arrests linear growth but also influences the psychomotor functioning of adolescents. 6 Numerous studies and reports [7][8][9][10][11] revealed that adolescents are at a greater risk of nutritional deficiencies and disorders due to their rapid body growth, unhealthy eating habits, psychological, mental and emotional pressures associated with body dissatisfaction and temptations to have a slimmer body. Adolescents also tend to suffer from a variety of eating disorders i.e., anorexia nervosa, bulimia nervosa as well as depression, anxiety and psychological stress.…”
mentioning
confidence: 99%